2020
DOI: 10.1186/s41927-019-0111-6
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of depression and anxiety in patients with ankylosing spondylitis: a systematic review and meta-analysis

Abstract: Background: As awareness for the importance of mental health continues to expand in rheumatology, it is important to understand the epidemiology of psychiatric complications in ankylosing spondylitis (AS) with the ultimate goal of future prevention and improved quality of care. This study aims to review evidence on the incidence and determinants of depression and/or anxiety among patients with AS. Methods: We searched Medline, Embase, Cochrane Database of Systematic Reviews, CINAHL Complete, and PsycINFO for f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 33 publications
0
34
3
1
Order By: Relevance
“…Interestingly, increased peripheral inflammatory markers were more common among anti-depressant non-responders compared with responders. 8 Furthermore, it is well 2846 (28) 3813 2531 291 257 226 174 215 (2) Other csDMARDs (%) 205 (11) 703 (7) 649 4382 (27) 929 (21) 366 (14) 166 (8) 292 (8) 74 7bDMARDs (17) 1554 (15) 2095 (14) 338 (24) 972 (22) 409 (16) 180 (8) 410 (11) 97 (10) Glucocorticoids (%) (12) 2394 (23) 3988 (26) 143 (10) 834 (19) 591 (23) 235 (11) 673 (18) 208 (21) bDMARD, biologic DMARD; cDMARD, conventional synthetic DMARD; DMARD, disease modifying anti-rheumatic drugs; TNF, tumour necrosis factor. 281 (6) 310 (5) 193 (17) 370 (12) 134 (10) 406 (20) 471 (14) 119 (13) Female (%)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, increased peripheral inflammatory markers were more common among anti-depressant non-responders compared with responders. 8 Furthermore, it is well 2846 (28) 3813 2531 291 257 226 174 215 (2) Other csDMARDs (%) 205 (11) 703 (7) 649 4382 (27) 929 (21) 366 (14) 166 (8) 292 (8) 74 7bDMARDs (17) 1554 (15) 2095 (14) 338 (24) 972 (22) 409 (16) 180 (8) 410 (11) 97 (10) Glucocorticoids (%) (12) 2394 (23) 3988 (26) 143 (10) 834 (19) 591 (23) 235 (11) 673 (18) 208 (21) bDMARD, biologic DMARD; cDMARD, conventional synthetic DMARD; DMARD, disease modifying anti-rheumatic drugs; TNF, tumour necrosis factor. 281 (6) 310 (5) 193 (17) 370 (12) 134 (10) 406 (20) 471 (14) 119 (13) Female (%)…”
Section: Discussionmentioning
confidence: 99%
“…18 Likewise, patients with AS and PsA showed higher rates of anxiolytic usage compared with patients with RA. So far, metaanalyses and cohort studies have shown higher odds for depression among patients with RA, PsA and AS [19][20][21][22] compared with the general population. Depression in rheumatic diseases has been associated with impaired health-related quality of life, 23 worse response to treatment and lower improvement in disease activity over time.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…In one meta-analysis, the pooled prevalence of depression in AS was reported to be 29%. 37 However, findings from this meta-analysis were largely driven by one large study from Taiwan comprising 11,701 patients, 39 which used the Elixhauser comorbidity index to record ICD-9 identified diagnoses of depression, 40 rather than direct assessment of mood using a validated scale/interview. Reliance on clinical diagnosis can lack temporal validity, provides no information on current symptom severity, and may underestimate prevalence due to subthreshold and undiagnosed depression.…”
Section: Prevalence and Incidence Of Depression In Patients With As Omentioning
confidence: 99%
“… 37 , 44 Comprising 5947 patients with AS from three studies conducted in Taiwan, Sweden and the United States (US), a pooled rate ratio (RR) for depression in AS was 1.51 (95% CI, 1.28–1.79). 37 This 51% increase in risk was calculated based on studies that report incidence rates within 1 year, 45 10 years, 46 and 13 years of developing AS. 47 Smoking and lower education were reported to be associated with a higher risk of depression.…”
Section: Prevalence and Incidence Of Depression In Patients With As Omentioning
confidence: 99%
“…9,10 AS is also known to be associated with depression, which could predispose affected individuals to dementia later in life. [11][12][13] Moreover, patients with AS could have limited physical activity which is another risk factor of dementia. 14,15 However, specific data on the relationship between AS and dementia are still conflicting.…”
mentioning
confidence: 99%